Insurance Companies in Emerging Markets - Kong, Janet; Singh, Manmohan (Washington, D.C. : International Monetary Fund, 2005)
This paper focuses on asset allocation decisions of life insurance companies in emerging markets. Mature market insurers allocate only a small fraction of their assets to emerging markets because of regulatory constraints, rating pressures, and currency risk. However, global insurers invest directly in emerging markets by setting up subsidiaries rather than through portfolio investment, and this trend is increasing. Local insurers largely remain captive investors of local instruments and provide stability to the domestic securities market. The regulatory regime and the liquidity and depth of local markets play an important role in asset allocation decisions of insurers. Insurance companies are increasingly adopting asset liability management and risk control measures. However, insufficiently developed local markets and regulatory interventions on the liabilities side often limit optimal asset allocation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet